Hunters of the mountain : the archaeology of Jebel Gharbi-Nefusa, northwest Libya, from the end of Pleistocene to the Holocene - Barich, Barbara E. (L'Erma di Bretschneider, 2024)
Purchase online the PDF of Hunters of the mountain, Barich, Barbara E., editor -
Keywords: Archéologie -- Djebel Nefousa

Landmarks of Identity: Bronze Age Towers of the Oman Peninsula - Döpper, Stephanie (The Archaeological Heritage of Oman, 2024)
Five thousand years ago, in the Early Bronze Age, monumental stone and mud-brick structures known as towers appeared on the landscape of the Oman Peninsula. Since then, they have served as distinctive landmarks of identity for the people of the region. Despite many years of archaeological research and intensive excavations of some of them, much remains unknown about these impressive structures. This book aims to update the long-standing discussions on these towers and to assess their chronological depth of more than a millennium, with the first of them constructed as early as the end of the 4th millennium BCE and the last substantial building activities at the beginning of the 2nd millennium BCE. The book also reassesses their possible functions, such as defence, refuge, demarcation of property, residence of elites, involvement in complex irrigation systems, arenas for cultic practices, in the light of recent archaeological research. The book will also provide a richly illustrated catalogue with extensive bibliography, research history and coordinates of all the nearly hundred towers known to date in the Sultanate of Oman and the United Arab Emirates, creating a record for researchers and visitors alike.
Keywords: Archéologie -- Oman

Landscapes of Death: Early Bronze Age Tombs and Mortuary Rituals on the Oman Peninsula - Kimberly D., Williams (The Archaeological Heritage of Oman, 2024)
This book provides a comprehensive and detailed review of the evidence for Early Bronze Age mortuary rituals on the Oman Peninsula, describing the research conducted, synthesizing the resulting data, and presenting a complete view of the state of knowledge on the topic. The author demonstrates that the construction, use, and location of mortuary cairns in the ancient landscape is no simple question in the Early Bronze Age archaeology of the region. This book explores the characteristics of ancient funerary monuments and rituals, demonstrating variations in these practices, as well as evidence for continued cairn use during this period and how some communities elaborated mortuary rituals. This book will serve as an invaluable reference volume for scholars working in the region, as an introduction for students to mortuary archaeology and to models that can be used to explore this aspect of prehistoric life on the Oman Peninsula, and as a valuable repository of currently available data. The book features extensive demonstrative illustrations and appendices summarizing the architecture, interments, and material culture found in all published Early Bronze Age mortuary monuments in the region.
Keywords: Archéologie -- Oman

Britain and the Dhofar War in Oman, 1963–1976: A Covert War in Arabia - Hughes, Geraint (Security, Conflict and Cooperation in the Contemporary World, 2024)
Keywords: Dhofar

ندوات إطلالت على كتاب: سلسلة جلسات ثقافية انعقدت في المكتبة الثقافية بقصر بني يزقن - غرداية - طلاي, إبراهيم بن محمد (مطبعة الآفاق, 2024)

Archaeological mission of Wadi Hasid (Sultanate of Oman) Discovering an Iron Age hillfort in the Ja’alan - Gernez, Guillaume; Gobron, Michael; Lenoir, Agathe; Fonteneau, Tom (Ministry of Heritage and Tourism, 2024)
Keywords: Archéologie -- Oman

القاموس الإداري والحكم المحلي: أمازيغي-عربي - بوزخار, مادغيس (المركز الليبي للدراسات الأمازيغية, 2024)
Keywords: Linguistique -- Djebel Nefousa

‏اتجاهات التفسير ومناهجه عند إباضية الجزائر من القرن 13 هـ إلى أوائل القرن 15 هـ - خبزي, دليلة (جمعية التراث, 2024)

‏جزيرة جربة: السكان تاريخهم ووثائقهم - الإنكشاري, الهادي بن يونس (منشورات التعارف, 2024)
Keywords: Djerba -- Histoire; Monuments -- Djerba; Sources -- Djerba

‏فهرس مخطوطات خزانة الشيخ محمد بن عيسى بن سعيد المرساوني النفوسي الليبي (‏المتوفى حوالي منتصف قرن 14هـ)، دفين جزيرة جربة تونس - الحاج موسى, بشير بن موسى; المزاوي, علي بن يوسف (سلسلة فهارس مخطوطات نفوسة, 2024)
Keywords: Bibliothèques -- Djebel Nefousa; Catalogue -- Djebel Nefousa; Manuscrits -- Djebel Nefousa

الأعمال الكاملة للآيام الدراسية العلمية: من الشيخ عمي سعيد بن علي الجري [ن 927 هـ/1521م] إلى الشيخ حمو بن موسي عمي سعيد [ت 1425 هـ/2005 م] مسيرة علمية تربوية اجتماعية ، عوية رائكة... ومتواصلة. أيام: 09-11 شوال 1427 ه / 01-03 نوفمبر 2006م مسجد بابا السعد الشرقي - غرداية - مؤسسة الشيخ عمي سعيد (مؤسسة الشيخ عمي سعيد, 2024)
Keywords: Biographies

الزرايب بجزيرة جربة: دليل علمي للصيد التقليدي = Zrayeb on the Island of Djerba : Practical guide to traditional fishing (Association Jlij pour l'environnement marin, 2024)
Keywords: Pêche -- Djerba

‏كتاب أعمل الملتقى الوطني: نظام العزابة نشأته ودوره الحضاري في بلاد المغرب - بحاز, إبراهيم بن بكير; حدبون, محمد بن قاسم (جامعة غرداية, 2024)
Keywords: Idées politiques -- Ibadisme

‏كتاب أعمال الدراسية العلمية عن الشيخين إبراهيم بن بكر حفار ومحمد بن بكر حفار من يوم الجمعة 16 ربيع الثاني 1444هـ/11 نوفمبر 2022م إلى يوم الجمعة 1 جمادى الأولى 1444هـ/25 نوفمبر 2022م بالتعاون مع مسجد بابا الشرقي غرداية - عشيرة آت علاهم القرارة - مجمع عشائر بني يزقن (مؤسسة الشيخ عمي سعيد, 2024)
Keywords: Biographies -- Mzab -- 20e siècle

‏مقالات الشيخ عدون في الصحافة الوطنية - بكوش, محمد بن موسى (جمعية التراث, 2024)
Keywords: Journalisme -- Mzab; Réformisme -- Mzab

‏بيان البيان القطب العلامة أمحمد بن يوسف أطفيش - أطفيش, محمد بن يوسف (دار الكنوز, 2024)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Coran -- Commentaires -- 19e siècle

‏جوابات وفتاوى في الدين والحياة: العقيدة العبادات المعاملات التربية الأحوال الشخصية - طلاي, إبراهيم بن محمد (مطبعة الآفاق, 2024)
Keywords: Fiqh -- Mzab -- 20e siècle

Le M'zab vallée de l'endurance : Histoire et vie sociale, étude qui donne un aperçu sur ce terroir et le vécu de ses autochton[es] - Ṭallāy, Ibrāhīm (Horizon Print, 2024)
Keywords: Moeurs et coutumes -- Mzab

Mzab Land of Strenuous Effort: Socio-Historical Description of the Establishement of the Region and the Life of Its Inhabitants - Ṭallāy, Ibrāhīm (Horizon Print, 2024)
Keywords: Moeurs et coutumes -- Mzab

‏وادي مزاب بلاد الكفاح: دراسة تاريخية اجتماعية تلقي أضواء على نشأت هذا البلد وحياة ساكنيه - طلاي, إبراهيم بن محمد (مطبعة الآفاق, 2024)
Keywords: Moeurs et coutumes -- Mzab

‏القول الوجيز في تفسير السور القصار من كتاب الله العزيز - طلاي, إبراهيم بن محمد (مطبعة الآفاق, 2024)
Keywords: Coran -- Commentaires -- 20e siècle

‏الحفيد السليم ابن بطوطة الصغير: ورواية - دادي عدون, محمد (دار الباحث للنشر والتوزيع, 2024)
Keywords: Littérature -- Mzab

‏العلامة امحمد بن يوسف أطفيش الجزائري قطب الأمة 1238-1332هـ - 1821-1914م حياته جهاده مواقفه - أوزايد, بالحاج بن عمر (جمعية التراث, 2024)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Biographies -- Mzab -- 19e siècle

تيرسين نات-مليشت= آبار آت مليشت: إرث الأجداد وقف للأحفاذ - باعمارة, سليمان بن أحمد (مؤسسة منارة الإيمان, 2024)
Keywords: Monuments -- Mzab; Puits -- Mzab

‏التعمير والمعمار بالجبال نفوسة خلال العصر الوسيط: دراسة اثنو أثرية وتاريخية - الزواري, محمد (GLD, 2024)
Keywords: Urbanisme -- Djebel Nefousa

‏هموم جزائرية مقابلات صحفية في قضايا ثقافية واجتماعية أجرتها صحف وطنية وإسلامية مع دكتور محمد صالح ناصر ما بين 1983-2007 - ناصر, محمد صالح (جمعية التراث, 2024)
Keywords: Journalisme -- Mzab

فهرس مخطوطات خزانة مكتية السلف بقصر آت مليشت للشيخ عمر بن الحاج عيسى بن باعمور المليكي (المتوفى بعد 1248هـ/1833م) ونجليه القاضي الحاج سليمان بن الشيخ عمر (ت. 1304هـ/1887م) والأمين بكير بن الشيخ عمر (ت. 1285هـ/1869م) - الحاج موسى, بشير بن موسى (فهارس المخطوطات, 2024)
Keywords: Bibliothèques -- Mzab; Catalogue -- Mzab; Manuscrits -- Mzab

المجتمع الإباضي بجنوب إفريقية: من أواسط القرن 5 الهجري/11م إلى نهاية القرن 9 الهجري/15م - بن غازي, البشير (دار الكتاب, 2024)
Keywords: Sources -- Ibadisme; Vie culturelle -- Afrique du Nord; Vie intellectuelle -- Afrique du Nord; Vie sociale -- Afrique du Nord; Vie sociale -- Ibadisme

Légendes des mosquées et des marabouts de Djerba - Chahed, Youssef (Arabesques, 2024)
Keywords: Littérature -- Djerba; Moeurs et coutumes -- Djerba

Society of the Righteous Ibadhi Muslim :Identity and Transnationalism in Tanzania - Wortmann, Kimberly T. (Indiana University Press, 2024)
Although the rule of the Omani sultanate in Tanzania came to an end following the Zanzibar Revolution in 1964, the legacy of its empire still exists today, along with its distinctive religious identity. The Ibadhi Muslims of Omani descent, who are neither Sunni nor Shi'a, have used a message of tolerance and harmonious coexistence to spread their beliefs across North and East Africa in a post-revolution and post-independence era. In Society of the Righteous, Kimberly T. Wortmann explores how the Ibadhi-Omani community in Tanzania has engaged in charitable activities, cooperation within the Muslim community, and economic development, despite facing suspicions of foreign influence and elitism. The focus is on the Istiqaama Muslim Community, an international charity network established in Oman and Tanzania in 1995. This ethnographic and transregional study documents the strategies employed by the "People of Truth and Righteousness" to preserve their unique religious practices and beliefs. Society of the Righteous moves beyond the typical discussions on global Muslim religion and politics, such as tradition versus modernity, conflicts between different branches of Islam, and the global war on terror. Instead, it explores the intricacies of a religious community whose significance has been obscured by the limitations of area studies paradigms. It illuminates the complexities of religious identity, transnational networks, gender relations, and the power of collective memory in shaping narratives of belonging, cultural preservation, and change in an increasingly interconnected world.
Keywords: Relations -- Oman -- Zanzibar; Relations -- Zanzibar -- Mzab; Tolérance religieuse -- Zanzibar

‏فلسطين أرض الحضارات: المدن والمواقع والإعلام - بورقو, المنجي (دار نقوش عربية, 2024)
Keywords: Question palestinienne

المخطوطات العمانية في مكتبة آل يدر في بني يزقن - وادي مزاب - الشيباني, سلطان بن مبارك (المخطوطات العمانية في الخزائن الجزائرية, 2024)
Keywords: Bibliothèques -- Mzab; Manuscrits -- Mzab

المخطوطات العمانية في الخزانة العامة بغرداية - وادي مزاب - الشيباني, سلطان بن مبارك (المخطوطات العمانية في الخزائن الجزائرية, 2024)
Keywords: Bibliothèques -- Mzab; Manuscrits -- Mzab

الحركة النسوية: الأصول الفكرية والآثار الأخلقية على الأسرة والمجتمع (المحتوى النظري للدورة التكوينية) - شخار, أبو نصر بن محمد (مؤسسة إنسان لأبحاث الفكر والمجتمع, 2024)
Keywords: Vie sociale -- Mzab

Constructing Oman’s Peaceful Identity: Alignment Strategies and Discursive Identifications Under Sultan Qaboos bin Said - Daga, Giulia (Middle East Today, 2024)
This book offers a comprehensive and insightful exploration of Oman’s discourses on foreign policy and national identity in the context of the Middle East. The Sultanate of Oman is often hailed as a peaceful exception in the region, but this work goes beyond surface-level observations to reveal the intricate complexities of Oman’s foreign policy and identity construction. With a keen focus on deconstructing essentialist understandings, the chapters delve into how discursive alignments and identity contents have shaped the government’s quest for legitimacy, recognition, and status. Employing a pioneering discourse historical approach to compare the National Day speeches and UN General Assembly speeches throughout Sultan Qaboos bin Said Al Bu Saidi’s reign (1970–2020), the author reveals how discourse evolved based on time, issues, and audiences. Notably, the book situates Oman within the context of the Gulf Cooperation Council states, examining how the Omani government’s interlinked discourses on identity and foreign policy contributed to differentiate the Sultanate from other Gulf countries. With chapters exploring Oman’s foreign policy principles, its material and ideological response to the ideas linked to the Dhofar Revolution, and its interactions with the Arab world and the international community, readers of this book will gain a comprehensive understanding of Oman’s evolving national and supranational identifications and the dynamic nature of its foreign policy. Challenging prevailing narratives while providing a fresh perspective on the relations between Oman’s foreign policy and identity construction, this book marks an important text for scholars as well as policymakers and anyone interested in understanding the intricate dynamics of Oman’s role in the global stage.
Keywords: Vie politique -- Oman -- 1970-2020

بصمات في الأدب العربي - حالو, أحمد عبد المنعم (ذاكرة عمان, 2024)
Keywords: Littérature -- Oman

Landmarks of Identity: Bronze Age Towers of the Oman Peninsula - Döpper, Stephanie (Archaeopress, 2024)
Five thousand years ago, in the Early Bronze Age, monumental stone and mud-brick structures known as towers appeared on the landscape of the Oman Peninsula. Since then, they have served as distinctive landmarks of identity for the people of the region. Despite many years of archaeological research and intensive excavations of some of them, much remains unknown about these impressive structures. This book aims to update the long-standing discussions on these towers and to assess their chronological depth of more than a millennium, with the first of them constructed as early as the end of the 4th millennium BCE and the last substantial building activities at the beginning of the 2nd millennium BCE. The book also reassesses their possible functions, such as defence, refuge, demarcation of property, residence of elites, involvement in complex irrigation systems, arenas for cultic practices, in the light of recent archaeological research. The book will also provide a richly illustrated catalogue with extensive bibliography, research history and coordinates of all the nearly hundred towers known to date in the Sultanate of Oman and the United Arab Emirates, creating a record for researchers and visitors alike.
Keywords: Archéologie -- Oman

Vocabulaire détaillé de la langue arabe - Mesure, Madeleine; Claver, Marie (El Jardín de la Voz Biblioteca de Literatura Oral y Cultura Popular, 2024)
Madeleine Mesure (Lille 1906 - Toulouse 1978) y Marie Claver (Compiègne 1890 - Toulouse 1985) fueron dos misioneras de nuestra Señora de África, “hermanas blancas”, que desarrollaron su labor en el Sáhara argelino. La primera permaneció entre 1930 y 1961 y tenía buenos conocimientos del árabe literal y argelino. La segunda de ellas desde 1914 hasta 1970, conocía muy bien el árabe argelino y literal y aprendió el amacige de los mozabíes. El original de la obra que editamos se encuentra en la Casa General de las Hermanas Blancas en Roma. Su contenido es, sobre todo, léxico, pero contiene también fraseología en árabe argelino e indicaciones y explicaciones en francés, después de los nombres en árabe argelino, sobre, por ejemplo, el tratamiento de enfermedades con plantas autóctonas, la ceremonia nupcial o el funcionamiento del telar. En su conjunto, podemos decir que es una descripción bastante amplia de la vida de las mujeres y hombres en el Sáhara argelino a partir de su variedad árabe y, en menor medida, amacige. Los dibujos que la acompañan fueron hechos por la hermana Claver. Reproducimos aquí el "Vocabulaire détaillé de la langue arabe" en las lenguas originales, francés, árabe y amacige, acompañado de una presentación en español.
Keywords: Linguistique -- Mzab

Zanzibari Muslim Moderns Islamic Paths to Progress in the Interwar Period - Bang, Anne K. (Hurst, 2024)
Zanzibari Muslim Moderns is a historical study of Zanzibar during the interwar years. This was a period marked by rapid intellectual and social change in the Muslim world, when ideas of Islamic progress and development were hotly debated. How did this process play out in Zanzibar? Based on a wide range of sources—Islamic and colonial, private and public—Anne K. Bang examines how these concepts were received and promoted on the island, arguing that a new ideal emerged in its intellectual arena: the Muslim modern. Tracing the influences that shaped the outlook of this new figure, Bang draws lines to Islamic modernists in the Middle East, to local Sufi teachings, and to the recently founded state of Saudi Arabia. She presents the activities of the Muslim modern in the colonial employment system, as a contributor to international debates, as an activist in the community, and more. She also explores the formation of numerous faith-based associations during this period, as well as the views of the Muslim modern on everything from funerary practices and Mawlid celebrations to reading habits. A recurring theme throughout is the question with which many Muslim moderns were confronted: who should implement development? And for whom?
Keywords: Réformisme -- Zanzibar

Zanzibar Was a Country: Exile and Citizenship between East Africa and the Gulf - Mathews, Nathaniel (University of California Press, 2024)
Zanzibar Was a Country traces the history of a Swahili-speaking Arab diaspora from East Africa to Oman. In Oman today, whole communities in Muscat speak Swahili, have recent East African roots, and practice forms of sociality associated with the urban culture of the Swahili coast. These "Omani Zanzibaris" offer the most significant contemporary example in the Gulf, as well as in the wider Indian Ocean region, of an Afro-Arab community that maintains a living connection to Africa in a diasporic setting. While they come from all over East Africa, a large number are postrevolution exiles and emigrés from Zanzibar. Their stories provide a framework for the broader transregional entanglements of decolonization in Africa and the Arabian Gulf. Using both vernacular historiography and life histories of men and women from the community, Nathaniel Mathews argues that the traumatic memories of the Zanzibar Revolution of 1964 are important to nation-building on both sides of the Indian Ocean.
Keywords: Emigration -- Zanzibar -- Oman; Vie politique -- Zanzibar -- 1963-1964; Vie politique -- Zanzibar -- 1964-1985

الكتاب المبين في الناسخ والمنسوخ (أنموذج مصنفات علوم القرآن) - الشيباني, سلطان بن مبارك (من هنا تشرق الشمس: نماذج إسهام العمانيني في المعارف الإنسانية, 2024)
Keywords: Coran -- Commentaires

رحلة البحث عن سبعين بدريا - الشيباني, سلطان بن مبارك (منشورات الوقف المبارك, 2024)
Keywords: Hadith

شجرة نسب العالمة المحقق الخليلي وأولاده وأحفاده - الشيباني, سلطان بن مبارك (تأريخ ما أغفله التاريخ من بطون المخطوطات, 2024)
Keywords: Biographies -- Oman

عود على بدء مع ديوان جابر بن زيد وكلام حايج خليفة في كشف الظنون - الشيباني, سلطان بن مبارك (ذاكرة القرن الأول للهجرة في عمان, 2024)
Keywords: Fiqh -- Irak -- 8e siècle

قصيدة الجني في غريب اللغة - الشيباني, سلطان بن مبارك (من نفائس المخطوطات المحفوظة في الخزائن العمانية, 2024)
Keywords: Poésie -- Oman

مِنْ أين لك هذا؟ - الشيباني, سلطان بن مبارك (ذاكرة القرن الأول للهجرة في عمان, 2024)
Keywords: Relations -- Oman -- Omeyyades

Ecrits berbères en fragments : édition bilingue français-kabyle - Lechani, Mohand Saïd (Geuthner, 2024)
Keywords: Linguistique -- Kabylie

المجتمع النفوسي خلال العصر الوسيط جدلية المحلي والوافد - الزواري, محمد (منشورات مقدمة, 2024)
Keywords: Moeurs et coutumes -- Djebel Nefousa

الوهابية الرستمية: نشأتها وتاريخها - آل الشيخ, عبد اللطيف بن عبد العزيز (2024)
Keywords: Polémique wahhabite -- 2000-....

L'orientalisme en train de se faire: une enquête collective sur les études orientales dans l'Algérie coloniale - Bossaert, Marie; Jomier, Augustin; Szurek, Emmanuel (En temps & lieux, 2024)
Keywords: Orientalisme -- France

Contemporary Oman: The Sultan, the People and the Stability - Zweiri, Mahjoob; Qawasmi, Farah Al (Gerlach Press, 2024)
At a time of rapid international change and marked regional dynamism, the Sultanate of Oman is emerging as a nation of surprising significance. Oman is a unique case of a Gulf state strategically and culturally located at a crossroads between the Indian Ocean, the Arabian Sea and the Persian Gulf. From this position, the Sultanate has developed its own political identity and pursued a unique foreign policy in the turbulent Middle East region, enabling the country to survive and overcome the challenges of the region. Over the years, the Sultanate has earned the title "Switzerland of the Middle East" due to its political neutrality and its prominent role as a regional mediator and peacekeeper. Renowned local and international authors as well as promising younger scholars present studies on the history, politics, economy and culture of Oman.
Keywords: Vie politique -- Oman -- 1970-2020

دور قبيلة مزاتة وفروعها في التاريخ، الحركة الإباضية ببلاد المغرب خلال العصر الواسيط - الهداجي, أيمن (المسيرة للنشر والتوزيع, 2024)
Keywords: Histoire -- Mazata

Oman's Transformation after 1970 - Peterson, John E. (Social, Economic and Political Studies of the Middle East and Asia, 2024)
Keywords: Vie politique -- Oman

‏فهرس مخطوطات ‏خزانة ‏الشيخ ‏سالم بن خلفان بن سعيد السيباني - السعدي, فهد بن علي (‏سلسلة فهارس ذكرت عمان لمخطوطات الخزائن العمانية, 2024)
Keywords: Bibliothèques -- Oman; Catalogue -- Oman; Manuscrits -- Oman

‏فهرس مخطوطات ‏خزانة ‏الشيخ سيف بن حمد بن محمد الخضوري - الراجحي, بدر بن سيف بن راشد (‏سلسلة فهارس ذكرت عمان لمخطوطات الخزائن العمانية, 2024)
Keywords: Bibliothèques -- Oman; Catalogue -- Oman; Manuscrits -- Oman

المخطوط العماني: التاريخ والتقاليد - العيسري, محمد بن عامر (ذاكرة عمان, 2024)
Keywords: A dépouiller

خزائن المخطوطات في عمان: التعريف بها وبنوادرها - السعدي, فهد بن علي (ذاكرة عمان, 2024)
Keywords: A dépouiller

ندوة ذاكرة السويق من حلال الوثائق الأهلية - السعدي, فهد بن علي (ذاكرة عمان, 2024)
Keywords: A dépouiller

إباضية إفريقية والبعث الثاني بجزيرة جربة القرن الرابع والخامس هجري: أعلامه، آلياته ومجالاته - لطيف, محمد العادل (زينب للنشر و التوزيع‎, 2024)
Keywords: Ibadisme -- Djerba

ملتقى الجيلاني بن الحاج يحيى لأعلام جربة 2022-05- الدورة الخامسة: 07 = Colloque Jilani Bel Hadj Yahia 5ème Session: 07-05-2022 - اللواتي, مهدي (جمعية صيانة جزيرة جربة, 2024)
Keywords: Médecine -- Djerba

Malentendues - Filali, Azza (Elyzad, 2024)
Emna, la quarantaine, avocate tunisienne, mariée, est chargée d'une mission visant à évaluer le degré de civisme et d'autonomie des femmes rurales dans un village conservateur de l'île de Djerba. Emna découvre des femmes menant une vie de peu, obéissant à des hommes dont la violence n'est pas remise en cause. Elle va surtout découvrir
Keywords: Littérature -- Djerba

تاريخ رقومة: كشف التاريخ الثانية منجيني إلى مكانجي ويليه تاريخ الرحلة إلى بر التنج للدولة العلية العربية السعيدية - الأموي, عبد العزيز بن عبد الغني (دار الفرقد, 2024)
Keywords: Récits de voyage -- Mozambique

العمانيون والتَّدافُع الاستعماري على إفريقيا - Wilkinson, John Craven (سلسلة الترجمات, 2024)
Keywords: Relations -- Oman -- Afrique de l'Est

الشيخ قاسم بن سعيد الشماخي واسرته في مصر: حياة ايمان وعطاء - بن يحياتن, ساسي بن عمر (اباديكا, 2024)
Keywords: Emigration -- Djerba -- Egypte

الوقف الثقافي الإباضي والمالكي في مصر دراسة مقارنة - مصلح, أحمد بن مهني (اباديكا, 2024)
Keywords: Bibliothèques -- Le Caire; Emigration -- Djebel Nefousa -- Egypte; Emigration -- Djerba -- Egypte; Emigration -- Mzab -- Le Caire; Manuscrits -- Le Caire

العلاقات السياسيَّة بين سلطنة زنجبار وبريطانيا (1890-1911م) (دراسة تاريخيَّة/ وثائقيَّة) - قطن, نادية بنت موسى (دار الفرقد للنشر والتوزيع, 2024)
Keywords: Relations -- Zanzibar -- Royaume-Uni

نساء البوسعيد والسلطة في زنجبار - علي, شيماء غنيمي (النادي الثقافي, 2024)
Keywords: Vie politique -- Zanzibar

A la découverte de Djerba : l'ile à la cinquième saison - Mchiri, Mabrouk; Fathallah, Jalel (Sotumedias, 2024)
Keywords: Tourisme -- Djerba